2018
DOI: 10.1007/s00701-018-3623-8
|View full text |Cite
|
Sign up to set email alerts
|

Posterior fossa meningioma with invasion of the internal acoustic canal

Abstract: Meningiomas of the posterior fossa may in one-third of the cases invade the IAC. Opening of the IAC in these cases was a crucial step for increasing the GTR. Despite the minimal increased risk of transient CSF leak, IAC opening was not associated with an increased risk of facial palsy or hearing loss in comparison to non-opening the IAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…The white, light blue, and blue columns represent normal, partial palsy, and complete palsy, respectively. meningioma in 174 patients (28). Therefore, in this study, we found an increased risk of ANP in PCM surgery, probably because the IAC is very close to the Dorellos canal and the risk of nerve damage during tumor manipulation is increased rather than the IAC invasion itself is dangerous (30)(31)(32).…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…The white, light blue, and blue columns represent normal, partial palsy, and complete palsy, respectively. meningioma in 174 patients (28). Therefore, in this study, we found an increased risk of ANP in PCM surgery, probably because the IAC is very close to the Dorellos canal and the risk of nerve damage during tumor manipulation is increased rather than the IAC invasion itself is dangerous (30)(31)(32).…”
Section: Discussionmentioning
confidence: 50%
“…Agarwal et al reported that there was no association between IAC invasion and CN deficit in 34 cerebellopontine angle meningioma surgeries (29). In addition, Peraio et al reported that tumor removal with intracranial IAC drilling did not increase the risk of CN injury in a study reporting the surgical results of posterior fossa meningioma in 174 patients (28). Therefore, in this study, we found an increased risk of ANP in PCM surgery, probably because the IAC is very close to the Dorellos canal and the risk of nerve damage during tumor manipulation is increased rather than the IAC invasion itself is dangerous (30–32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noted that ear preference strength has been mapped to audiometric interaural threshold difference (33), and the DHI is a validated instrument. Whereas the study cohort is not the largest to report audiovestibular outcomes in posterior fossa meningioma (24,9), it is the only study to examine long-term hearing, tinnitus, balance, and quality of life in an integrated manner, as most other studies focus on perioperative complications or Karnofsky performance status. The large difference in response rates between the two cohorts is notable as well.…”
Section: Discussionmentioning
confidence: 99%
“…Suboccipital/ retrosigmoid approaches are most commonly employed in most case series and constitute a plurality of approaches utilized in the present series. Some authors have reported good results exclusively utilizing the retrosigmoid approach [6,11,12]. Other approaches to these tumors reported in the literature include trans-petrosal approaches (including translabyrinthine, transcochlear, combined petrosal, extended middle fossa / 'Kawase' approaches, etc.…”
Section: Choice Of Approachmentioning
confidence: 99%